Toward the Development of a Self-Management Intervention to Promote Pro-Social Behaviors for Students With Visual Impairment. (November 2016) - Ivy, Sarah E.; Lather, Amanda B.; Hatton, Deborah D.; Wehby, Joseph H.
Students with visual impairment (VI) lack access to the same models and reinforcers as students with sight. Consequentially, behaviors that children with sight acquire through observation must be explicitly taught to children with VI. In addition, children with VI have difficulty maintaining such behaviors. Therefore, interventions that promote self-management of students' own behavior are desirable. In this study, three adolescents used self-talk to increase chewing with a closed mouth during mealtimes. We used explicit instruction to teach students the target behavior and to use a small vibrating device as a reminder to self-talk during mealtimes. Prompts were faded as participants increased chewing with a closed mouth. Following mealtimes, performance feedback and reinforcement were provided. All students increased percentage of intervals chewing with a closed mouth immediately at the start of intervention and maintained this behavior for up to 1 month post-intervention. Implications for practice and directions for future research are discussed.